Strategi Talent Management Pada Usaha Kecil Dan Menengah Dalam Meningkatkan Daya Saing Bisnis - Lenny C Nawangsari; Achmad H Sutawidjaya (Indonesian Journal of Cultural and Community Development, 2018)
Dynamic business conditions, uncertainty and complexity require Small and Medium Enterprises (SMEs) to improve their strategy to exist in the business world. One of the important factors in business competition is the qualified Human Resources (HR). The good Management of human resource talent will be an added value for business competition. This study aims to analyze talent management strategies in SMEs to improve business competitiveness. The research methodology used a qualitative approach using case study. Data obtained through interviews and field observations on 5 key informants in SMEs belonging to members of PAUB (Women Interfaith) in Malang. The results of the study found that the SME management talent strategy consists of talent planning, talent recruitment, Talent Development and Talent Retaining. Talent Management strategy development should pay attention to corporate strategy and external environment that affect the condition of SMEs. Talent Management Strategy if applied properly is expected to improve SME productivity and profitability so that will lead to SME business continuity.